Development of Articulate Storyline-Based Learning Media on Heat and Temperature - Sukariasih, Luh; Anas, Muhammad; Rahayu, Diah Putri; Tahang, La; Fayanto, Suritno (FKIP Universitas Lampung, 2022)
This study aims to develop multimedia using articulate storyline software that can be accessed using smartphones or other devices such as computers. The study used a research and development design created using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The limited trial sample consisted of 15 Class VII SMP Negeri 1 Meluhu. Data collection techniques using interviews, checklists, and tests. The instruments used are validation sheets, student and teacher response questionnaire sheets, and learning outcomes tests. The results showed: (1) the validity of multimedia using the Aiken index (V) obtained the average value of the validation results of 0.78; (2) the effectiveness by using the n-gain test obtained a value of 0.56 and the percentage value of the effectiveness of 66.67%; (3) the practicality of the multimedia teacher response assessment obtained the practicality percentage of 90% and the practicality percentage of the student response obtained by 86.56%. Therefore, learning media can be used as teaching media based on the analysis results. Keywords: multimedia, articulate storyline, android. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1057-1068